METHYLHOPANOIDS: MOLECULAR INDICATORS OF ANCIENT BACTERIA AND A PETROLEUM CORRELATION TOOL - Farrimond P.; Talbot H.M.; Watson D.F.; Schulz L.K.; Wilhelms A. (My University, 2004)
Methylhopanoids are organic compounds synthesized by certain bacteria, that when preserved in sediments act as molecular fossils or biomarkers for organic matter inputs from specific bacterial sources. Two series of methylhopanoids occur, each mainly deriving from a distinct bacterial source: cyanobacteria (2-methyl) and methanotrophic bacteria (3-methyl). The abundance and composition of methylhopanoids within sediments of modern depositional environments varies widely, apparently due to different bacterial communities contributing to the sedimentary organic matter. Comparable molecular characteristics are found in oils and their source rocks. Consequently, methylhopanoids are valuable in oil-oil and oil-source rock correlations, distinguishing between samples related to different depositional environments. In particular, abundant 3β-methylhopanoids (from methanotrophic bacteria or an additional unknown bacterial source) are characteristic of some modern alkaline saline lake environments. Comparable compositional features in the methylhopanes of oils allow the assignment of lacustrine oils offshore West Africa to two distinct lacustrine source rock facies, and to distinguish between different marine source facies, thus refining oil-source rock correlation.